THE DEVELOPMENT OF CROSS-BORDER TOURISM CLUSTERS: STRATEGIC INITIATIVES AND MARKETING SUPPORT - POPADYNETS, Nazariy; NEZVESHCHUK-KOHUT, Tetyana; DANYLO, Yaroslav; BILETSKA, Natalia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
Tourism development in border regions is characterized by a number of features, among which favorable geographic conditions play a significant role, facilitating the attraction of both domestic and foreign tourists. This, in turn, helps to provide employment for the local population, increase revenues to local budgets, and improve the socio-economic indicators of border areas. Effective use of regional marketing tools and the application of marketing research results in the field of tourism services can solve many existing problems in this sector. This article focuses on the necessity for balanced tourism development through comprehensive marketing support, which includes a range of components from regulatory to informational resources. It analyzes the pivotal role of the informational segment in enhancing marketing effectiveness. Compared to international practices, particularly in European Union countries where marketing strategies are implemented to support and develop tourism, Ukraine exhibits a notable lack of experience in formulating national marketing strategies. The development and integration of pilot marketing strategies at the regional level are recommended. The importance of forming cluster initiatives and clearly defining the functions of a tourism cluster as key directions for stimulating regional tourism development is highlighted. This study examines strategic initiatives for the development of cross-border tourism clusters, which involve a series of actions aimed at promoting and optimizing cluster operations. Key measures include conducting training, participating in tourism fairs, developing websites, as well as organizing themed tours and cultural events. The importance of developing an effective marketing strategy based on detailed forecasting of the tourism sector's development is outlined, which should include an analysis of current trends and the impact of external factors. It is determined that the success of a marketing strategy will depend on measures that help mitigate negative industry trends and enhance tourist attraction. The necessity of monitoring to assess the effectiveness of strategic initiatives and adjust actions in the future is emphasized. The need to create a system of indicators to evaluate the performance of the tourism sector in the region is highlighted, which will ensure the long-term development of tourism through targeted implementation of marketing strategies.
Keywords: cluster; marketing; efficiency; strategy; tourism; tourism potential; cross-border regions; region; pandemic; sustainable development; international cooperation; foreign investments; Internet marketing; globalization